2021
DOI: 10.3390/ijms22030984
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ-1 Induced Cross-Linking of the Extracellular Matrix of Primary Human Dermal Fibroblasts

Abstract: Excessive cross-linking is a major factor in the resistance to the remodelling of the extracellular matrix (ECM) during fibrotic progression. The role of TGFβ signalling in impairing ECM remodelling has been demonstrated in various fibrotic models. We hypothesised that increased ECM cross-linking by TGFβ contributes to skin fibrosis in Systemic Sclerosis (SSc). Proteomics was used to identify cross-linking enzymes in the ECM of primary human dermal fibroblasts, and to compare their levels following treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 74 publications
2
9
0
Order By: Relevance
“…Transforming growth factor-β (TGF-β) is a key regulator of ECM biosynthesis [ 53 ]. Especially, the TGFβ/Smad pathway is mainly responsible for the collagen synthesis in human dermal fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transforming growth factor-β (TGF-β) is a key regulator of ECM biosynthesis [ 53 ]. Especially, the TGFβ/Smad pathway is mainly responsible for the collagen synthesis in human dermal fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Especially, the TGFβ/Smad pathway is mainly responsible for the collagen synthesis in human dermal fibroblasts. TGF-β controls collagen homeostasis by regulating the Smad pathway [ 53 ]. First, TGF-β binds to a TGF-β type II receptor (TβRII), which can be associated with a TGF-β type I receptor (TβRI) and lead to its phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CAFs generate contractile forces on the ECM, which is known to result in the release and activation of TGF-β1 [ 179 ], and activation of TGF-β signalling in fibroblasts, which in turn upregulates various cross-linking enzymes in the ECM, including TG2 that has a further impact on the biomechanical environment by increasing tissue stiffness [ 96 ]. Mechanical stresses can also directly induce and stabilize an open catalytically active conformation of TG2; hence, active TG2 results in a cross-linked ECM that can act as a storage depot for TGF-β [ 180 ].…”
Section: Tg2 Is Key To the Biomechanical Progression Of Cancermentioning
confidence: 99%
“…It is reported that TGF-β induced the upregulation of Wnt/β-catenin signalling in hypertrophic scar and keloid fibroblasts. The role of TGFβ in impairing ECM remodeling and antiangiogenic resistance ( Baek et al, 2001 ) has been demonstrated in various fibrotic models ( Semkova and Hsuan, 2021 ).…”
Section: Discussionmentioning
confidence: 99%